Corporate security career progression: A comparative study of four Australian organisations - Brooks, David J. (2019)
© 2019, Springer Nature Limited. The study investigated the Corporate Security stratum of work within large Australian organisations, seeking to extract professional seating, roles, associated task complexity, career opportunity and progression ceilings as articulated through the socio-organisational literature. Two phases were applied: Phase One used online surveys distributed to participants (N = 53) across four Australian organisations, Phase Two employed semi-structured interviews and focus groups (N = 14). Findings reinforced the established literature articulation of corporate security’s roles; however, they contested the current articulation of corporate security’s executive level seating within large organisations. Instead, the study identified a Corporate Security seating with a restricted sphere of risk-based influence, along with a maximum career level at general manager. The study demonstrates an occupational corporate security ceiling, debunking the security executive belief. Corporate security was located within the technostructure group as a specialist, limiting opportunity for executive level roles or strategic influence